LEJONG TAU, A DIORAMA OF CONFLICT RESOLUTION BASED ON LOCAL WISDOM - Kurniawan, Faizal (University of Muhammadiyah Malang, 2019)
This study aims to find out in depth the meaning of Lejong that defines ?visiting?,typical local wisdom of Manggarai. Lejong is convinced as an effort to solve theconflict faced by Manggarai?s students in Malang. This research was conducted onsome of Manggarai?s student communities in Malang, including IKAMMA, IMAMA,and others. This research focused on students who carried out the only Lejongactivities, opened in depth about the meaning of Lejong as the local identity of theManggarai community, especially in conflict management.The results of this study are the existence of local values accepted in the identity ofthe Manggarai community that has been rooted for a long time ago. It is undoubtedthat the role of senior in upholding the local identity of the Manggarai community,who are overseas, is also one of the ?effective ways? in resolving conflicts thatoccur between Manggarai?s students in Malang. This research is limited only tothe Manggarai?s students. The hope of this research is to contribute to the study ofliterature on conflict resolution based on local wisdom.